Analisis Potensi Wisata Desa Pandean Kecamatan Gondang Kabupaten Nganjuk Sebagai Desa Wisata - Badai Elsadhai Budiarti; Qonita Lindawati; Avita Agustin Listiawan; Jonathan Alfino Julianto Mangar; Firmansyah Firmansyah (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Pandean is one of the villages in Gondang District, Nganjuk Regency. This village is one of the largest shallot producers in Nganjuk. In addition, Pandean also has community’s small bussiness and also tourism attraction that can support it to become a tourist’s attraction in Pandean Village. The natural potentials in Pandean Village can be used as the main attraction of Pandean, agrotourism. With good management and routine training, Pandean Village can be used as a tourist village that competes with other tourist villages, especially in the East Java.